Investigation of space-energy effects in the reactivity measurement by neutron noise with excore detectors in a reflected LWR - Lescano, Vicente Horacio; Behringer, Klaus (Pergamon Press Ltd., 1982)
Fil: Lescano, Vicente Horacio Comisión Nacional de Energía Atómica; Argentina